ICT-Based Teaching-Learning Tools Used in ELT - Shahi , Dhurba Kumar (AMC Multidisciplinary Research Journal, 2025)
Information and Communication Technology (ICT) has revolutionized education, particularly in the field of English Language Teaching (ELT), by providing diverse tools for creating dynamic and interactive learning environments. This review-based research paper explores ICT-based teaching-learning tools and their impact on ELT, drawing on a wide range of studies to analyze their efficacy, applications, and challenges. Key ICT tools such as computers, mobile phones, tablets, digital recorders, interactive whiteboards, and traditional yet versatile devices like radios and televisions are examined for their contributions to enhancing language learning. ICT tools are instrumental in providing authentic learning materials, fostering collaboration, and enabling student-centered, self-directed learning. They support various educational activities, including lesson preparation, classroom interaction, feedback, and assessment, while offering learners the flexibility to engage with resources anytime, anywhere. Emerging concepts like Mobile-Assisted Language Learning (MALL) highlight how mobile devices personalize and enrich learning experiences, making language acquisition more accessible and effective. The findings demonstrate that ICT facilitates better access to information, promotes critical thinking, and enhances learner motivation through multimedia capabilities. Furthermore, ICT enables the transformation of traditional educational practices into digital, collaborative, and lifelong learning frameworks. Despite its potential, effective integration of ICT in ELT requires addressing challenges such as infrastructure development, teacher training, and stakeholder awareness. This paper concludes that ICT tools are indispensable in modern ELT, bridging educational gaps and offering innovative approaches to language instruction. Future research should focus on optimizing ICT integration, ensuring equity, and developing strategies for overcoming barriers to its effective use in diverse educational contexts.